The Using of Google Form for Digital Evaluation for Senior High School English Teacher Association, Hulu Sungai Utara, South Kalimantan - Tenny Murtiningsih; Yansyah Yansyah; Hafizhatu Nadia (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2021)
The development of technology also gives positive effect for education. One of them is the using of google form in education. Google form is one of online application that is used to collect the data of questionnaires. Nowadays, we can use it in education sector. That is for digital evaluation at school. The using of google form for digital evaluation is so effective. That’s why this community service gives training of the google form using for digital evaluation for Senior High School English Teacher Association, Hulu Sungai Utara, South Kalimantan. So they can use this application for English evaluation in their class. Some teachers who as the volunteer for this community service were interested to learn how to use this application. They practiced a lot during the training and at last they understand how to apply it for digital evaluation in their class. So next their English evaluation becomes English digital evaluation by using google form.